Microanatomical Studies on the Rete Testis of the Emu (Dromaius novaehollandiae) - Rajendranath, N.; Rao, T. S. Chandrasekhara; Kumar, D. Pramod; Raghavendar, K. B. P.; Kumar, Girish (Indian Journal of Veterinary Anatomy, 2013)
The rete testis was composed of intratesticular, intracapsular and extra testicular portion. The intratesticular rete were lined by a single layer of cuboidal or columnar cells. The intracapsular and extra testicular rete were lined by simple squamous or cuboidal epithelium. The alkaline phosphatase and acid phosphatase activities were intense in the rete channels.